Editorial Vol.7(1) - Ahmed, Tahera (Bangladesh Journal of Bioethics, 2016)
Greetings to all our honourable Readers and writers of the Bangladesh Journal of Bioethics! This issue of 2016 deals with the topic of Ageing and ethical issues related to the caring and respect of the elderly.